Controlling Inflation : The Problem of Non-Indexed Debt. (IMF Working Papers; Working Paper, 1988)
We show that the presence of nominal non-indexed government debt could give rise to more than one equilibrium inflation rate. Conditions for this to occur are discussed in terms of ad hoc and micro-founded models. Solutions to the indeterminacy problem are examined; one solution is shown to be price indexation of debt instruments.